Kinder- und Familienarmut: Lebensumstände von Kindern in der Grundsicherung. - (:unkn) unknown (My University, 2015)
In 2013, in about one third of all households with unemployment benefit II receipt there lived children under the age of 15. Children particularly often have to rely on basic social benefits. The proportion of children living in households at risk of income poverty amounted to 20 percent based on the Panel Study "Labour Market and Social Security". Applying both concepts of operationalising poverty, income poverty and benefit receipt, 76 percent of children in Germany live in households with a secured financial position, whereas 24 percent grow up in households that are either income-poor and / or receive unemployment benefit II. In general, very young children those with two or more siblings and those living in a single-parent family have a higher risk of growing up in households with unemployment benefit II receipt. Furthermore, children are more likely to grow up in households with unemployment benefit II receipt if their parents have a lower educational level, a migration background or if they have lower labour market participation. In comparison to the situation of children living in families with a secured financial position, the living conditions of children in families with unemployment benefit II receipt in terms of availability of goods and opportunities to social and cultural participation are characterized by an undersupply in almost all areas considered. However, in the availability of basic goods only slight differences occur. Thus, even in households with unemployment benefit II receipt the supply of basic necessities is assured. In the area of social and cultural participation and in higher-value consumer goods the deprivation can be considered higher and also differs more strongly from the situation of children who grow up in households with secured financial positions. It is also apparent that financial reserves can hardly be formed and unexpected expenses can rarely be overcome. The situation of children in lower income situations is rather unchanged since 2009.
Keywords: Sozialwesen; Armut; Versorgung; Sozialpolitik; Sozialrecht; Kinderarmut; Teilhabe; Grundsicherung; Sozialgesetzbuch II; Sozialgesetzgebung